RELATIONSHIP BETWEEN BUSINESS EDUCATORS’ PERCEIVED ADMINISTRATIVE LEADERSHIP STYLE AND THEIR JOB PERFORMANCE IN TERTIARY INSTITUTIONS IN TARABA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study determined the relationship between business educators’ perceivedadministrative leadership style and their job performance in tertiary institutions inTaraba State. One research question guided the study and one null hypothesis wastested at 0.05 level of significance. Correlational survey design was adopted for thestudy and the population was 79 business educators in tertiary institutions in TarabaState. A structured questionnaire developed by the researchers and validated byexperts was used for data collection. The measure of internal consistency method wasused to test the reliability of the instrument and data analysis with Cronbach Alphayielded a reliability coefficient of 0.82. Data collected from the study were analyzedwith Pearson Product Moment Correlation for the research question and hypothesisusing Statistical Package for Social Sciences (SPSS). The result showed that therewas negative relationship between business educators’ perceived autocraticadministrative leadership style and their job performance in tertiary institutions inTaraba State, however, the relationship was not significant. Based on the findings, itwas concluded that applying the democratic style of leadership will lead to increasedeffectiveness and efficiency of business educators in the institutions. The researchersrecommended that administrators should adopt the democratic leadership style morethan autocratic leadership style to enhance business educators’ quality jobperformance which will lead to the achievement of the objectives of the programme intheir institutions.
Keywords: Business educators, leadership, leadership style and job performance